Playing a video game is more than mere procrastination - Nordby, Kent (BMC Psychol, 2019)
BACKGROUND: Procrastination is seen as a severe problem among young people, and many factors have been claimed to be associated with it, playing video games being one of them. One of the reasons why video games might be related to procrastination is their ability to offer instant gratification and feedback, while at the same time offer distractions from less tempting and rewarding tasks. It is not yet agreed on whether or not video game players are more prone towards procrastination and discounting of future rewards. METHOD: Over 500 participants across two studies completed two surveys on video gaming habits, as well as a measurement of procrastination tendencies. In study 1 participants performed an experiential discounting task, while participants in study 2 performed the 5-trial adjusting delay discounting task, both tasks assessing preference for delayed larger rewards. RESULTS: In study 1, hours of videogaming was not significantly related to procrastination or the discount rate. In study 2, hours of videogaming was not strongly associated with procrastination and delay discounting either. However, when asked why they play, those answering to escape reality and to reduce stress had more problems of procrastination than those who play for entertainment, reward or social reasons. Overall, the association between procrastination and hours spent playing video games was weak but positive, r(513) = .122. DISCUSSION: Time spent enjoying and engaging in video gaming is done for various reasons, only for a few this is related to procrastination. By using only hypothetical payouts in the discounting tasks, the absence of a relationship between hours spent video gaming, procrastination and delayed gratification requires further investigation. However, playing video games is more than mere procrastination.